SYSTEMATIC POSITION OF ANTIARCHS (VERTEBRATA, PLACODERMI) FROM THE FAMENNIAN OF TVER REGION, RUSSIA - S. V. Moloshnikov; V. V. Linkevich (Известия высших учебных заведений: Геология и разведка, 2017)
New materials of the placoderm fish Bothriolepis heckeri Luksеvics from the Famennian of the Bilovo locality (Tver Region) are studied. This species is very similar to Livnolepis zadonica (H.Obrucheva) in the structure of cranial and postcranial armours and should be referred to the genus Livnolepis Moloshnikov. Morphoiogical simiiarities of these two species are discussed. Only bothriolepidids are really known in the Famennian of Tver Region. Data on the presence of asterolepidids (Asterolepis sp.) in the Middle Famennian need an additional evidence.